Modular construction of compact Petri net models. (2017) - Latorre-Biel, Juan Ignacio; Jiménez-Macías, Emilio; García-Alcaraz, Jorge Luis; Muro, Juan Carlos Sáenz-Díez; Blanco-Fernandez, Julio; Parte, Mercedes Pérez De La
The use of modelling formalisms for the design of discrete event systems presents many advantages, such as the possibility of structural analysis of the model or performance evaluation. However, the difficulty of the process to obtain an appropriate model of the system requires the use of methodologies to ease the work of the designers. In this paper, two main subjects are discussed. On the one hand, the modular construction of Petri nets alleviates the design process by the use of blocks that can be assembled to build up a complete Petri net model. On the other hand, the development of decision support systems may require the assessment of the performance and properties of complete models obtained from different combinations of modular blocks. The formalism of the alternatives aggregation Petri net may help in the development of compact and efficient models that may reduce the use of scarce computer resources.